Seasonal Variations in the Starch Properties of Sweet Potato Cultivars - dos Santos, Thaís Paes Rodrigues [UNESP]; Leonel, Magali [UNESP]; de Oliveira, Luciana Alves; Fernandes, Adalton Mazetti [UNESP]; Leonel, Sarita [UNESP]; da Silva Nunes, Jason Geter [UNESP] (My University, 2023)
Starch is widely used in the food and non-food industries, and this is related to its physicochemical characteristics. In the coming years, climate changes will become unpredictable, and these conditions may affect the process of starch biosynthesis and polymer properties. The sweet potato starch market has grown substantially in recent years and understanding the environmental impacts on starch characteristics will contribute to advances for the sector. Herein, the effects of the growing season on the structural, morphological, and physicochemical properties of sweet potato starches were evaluated. Sweet potato trials with two Brazilian cultivars (Canadense and Uruguaiana) were installed in the dry season (planting in March and harvesting in July) and rainy season (planting in October and harvesting in March). Regardless of the cultivar, starches isolated from plants grown in the rainy season have a more ordered structure, with higher gelatinization temperatures, thermal stability, and resistant starch content. Starches from plants grown in the dry season have a higher percentage of small granules with lower crystallinity and lower gelatinization temperatures. These findings can be useful as early knowledge of these changes can help the supply chain to better plan and target suitable markets for naturally modified sweet potato starches.
Keywords: growing season; Ipomoea batatas (L.) Lam; native starch; physicochemical properties